DEVELOPING STUDENTS’ LISTENING SKILL THROUGH VoA (VOICE OF AMERICA) LEARNING ENGLISH VIDEO - Dian Astuti; Muhammad Zuhri Dj; Musfirah Musfirah (Didaktika : Jurnal Kependidikan, 2019)
The purpose of this study was to investigate whether or not the students’ listening skill can be developed through VoA (Voice of America) Learning English Video. The samples of this study were 40 students from XI IIS of MAN I Bone taken from 424 students of MAN I Bone. The Pre-Experimental study was used in this research. Writing test was used to collect the data in this study. Based on the result of the data, can be stated that the students’ listening skill can be developed through VoA (Voice of America) Learning English Video. The students’ average score before giving treatment through VoA (Voice of America) Learning English Video was 50,05, while the students’ average score after giving treatment was 77,40. Based on the result of the students’ average score in Pre-Test and Post-Test showed that there was a development on students’ listening skill after giving treatment through VoA (Voice of America) Learning English Video.Keywords: listening skill, voice of America, learning English video